1995
DOI: 10.1183/09031936.95.08071076
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistant tuberculosis in northern Germany: a retrospective hospital-based study of 1,055 patients from 1984 until 1993

Abstract: D Dr ru ug g--r re es si is st ta an nt t t tu ub be er rc cu ul lo os si is s i in n NWe reviewed the medical records of all patients with positive cultures for Mycobacterium tuberculosis from 1984 until 1993 in a hospital near Hamburg. Drug-susceptibility testing was performed for isoniazid, rifampicin, ethambutol, and streptomycin, using the modified proportion method.Of 1,055 patients, 9.6% had isolates resistant to one or more drugs. Of the isolates, 5.8% showed resistance to isoniazid or rifampicin and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…As opposed to the USA, in European countries, such as the UK [10] and Spain [11][12][13], the prevalence of tuberculosis resistant to treatment has not risen in recent years. In Germany, the data from two recent studies are not consistent [14,15].…”
mentioning
confidence: 59%
“…As opposed to the USA, in European countries, such as the UK [10] and Spain [11][12][13], the prevalence of tuberculosis resistant to treatment has not risen in recent years. In Germany, the data from two recent studies are not consistent [14,15].…”
mentioning
confidence: 59%
“…HIV has been found to be a risk factor for resistance in the United States [5,[7][8][9] but not in Africa [10]. Some studies have found resistance to be associated with cavitatory pulmonary disease [11], and most studies from developed countries (particularly the United States) have found relationships with ethnic groupings [5,7], foreign birth [7,[12][13][14] and urban centres [13]. In the United Kingdom surveillance data from England and Wales have generally shown an excess of drug-resistant cases in London, in HIV-positive cases, those not born in the United Kingdom and sometimes in non-white ethnic groups [2,3,15].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the United States discovered that HIV infection was also a risk factor for resistance [9][10][11][12][13]. Other risk factors reported included foreign birth, ethnicity, living in urban centers, and having cavitary pulmonary tuberculosis [9,11,[14][15][16][17]. However, most of these studies were conducted in developed countries, particularly in the United States and European countries.…”
Section: Introductionmentioning
confidence: 99%